Gastric Emptying and Intragastric Behavior of Breast Milk and Infant Formula in Lactating Mothers. Issue 12 (29th September 2021) - Camps, Guido; van Eijnatten, Elise J M; van Lieshout, Glenn A A; Lambers, Tim T; Smeets, Paul A M
ABSTRACT: Background: When sufficient breast milk is not available, infant formula is often used as an alternative. As for digestion, gastric behavior of infant formula and breast milk have not been studied in detail. Objective: This study aimed to compare gastric emptying and intragastric behavior between breast milk and infant formula in vivo using MRI. Methods: In this randomized crossover study, 16 lactating mothers (age: 31.7 ± 2.9 y; time since giving birth: 9.3 ± 2 mo), underwent gastric MRI scans before and after consumption of 200 mL of infant formula or their own breast milk. MRI scans were performed after an overnight fast (baseline) and every 10 min up until 60 min following ingestion. Primary outcomes were gastric emptying measures and the secondary outcome was gastric layer volume over time. Differences between infant formula and breast milk in total gastric volume and layering volume were tested using linear mixed models. Results: Gastric emptying half-time was 5.1 min faster for breast milk than for infant formula (95% CI: –19.0 to 29.2) ( n = 14). Within a subgroup ( n = 12) with similar initial gastric volume (<20 mL difference), gastric emptying half-time was 20 min faster for breast milk (95% CI: 1.23–43.1). Top layer volume ( n = 16) was 6.4 mL greater for infant formula than for breast milk (95% CI: 1.9–10.8). This effect is driven by t = 10 and t = 20 min postingestion. Conclusions: When taking initial gastric volume into account, breast milk emptied faster than infant formula in women, which is in line with previous findings in infants. Infant formula showed a significantly larger top layer volume in the first 20 min after ingestion. MRI in adults may find application in studies assessing gastric behavior of infant formula.